KARAKTERISASI PATI BIJI BUAH DURIAN, BIJI BUAH NANGKA, DAN BIJI BUAH ALPUKAT - R Herni Kusriani (JURNAL FARMASI GALENIKA, 2014)
Starch as one of the excipients in the pharmaceutical plays an important role. One of the source of starch that is widely used is from cassava. This study aims to look for other sources of starch from local materials which can ensure the quality and availability, such as the seeds of durian, jackfruit, and avocado. The methods of this research include the characterization of starch and proximate analysis (moisture, ash content, fat content, protein content, and fiber content). The results showed that the starch from grains rendemen durian, jackfruit, and avocados were respectively 10, 16, and 4%. Proximate analysis showed that the protein content of the starch grains durian, jackfruit,and avocado respectively were 14.58; 13.56; and 17.13%, while the fat content of starch grains durian, jackfruit, and avocado respectively were 3.55; 3.68; and 4.95% and fiber content of starch grains durian, jackfruit, and avocado were 8.80; 8.55; and 9.10%. It was concluded that macronutrient containsof avocado seed greater than durian and jackfruit seeds, although rendemen of avocado seed starch was lower than durian and jackfruit seed.